2021
DOI: 10.1523/eneuro.0101-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Tactile Sensory Systems Share Common Features in Object Recognition

Abstract: Although we use our visual and tactile sensory systems interchangeably for object recognition on a daily basis, little is known about the mechanism underlying this ability. This study examined how 3D shape features of objects form two congruent and interchangeable visual and tactile perceptual spaces in healthy male and female participants. Since active exploration plays an important role in shape processing, a virtual reality environment was used to visually explore 3D objects called digital embryos without u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
2
9
2
Order By: Relevance
“…These results may seem to contradict a recent study by Tabrik et al (2021) . In that study, a great deal of similarity was found between the chosen shape metrics and the self-reported measures of perceptual similarity in both within-modal visual and within-modal haptic comparisons (different groups of participants were used for these tasks, so no cross-modal comparisons were possible).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These results may seem to contradict a recent study by Tabrik et al (2021) . In that study, a great deal of similarity was found between the chosen shape metrics and the self-reported measures of perceptual similarity in both within-modal visual and within-modal haptic comparisons (different groups of participants were used for these tasks, so no cross-modal comparisons were possible).…”
Section: Discussioncontrasting
confidence: 88%
“…For example, it was possible (though exceedingly unlikely) to have the same shape presented five times in a row. Consistent with previous experiments comparing visual and haptic stimuli ( Newell et al, 2001 ; Lacey et al, 2007 , 2009 ; Tabrik et al, 2021 ), participants were given double the time to explore haptic (6 s) as visual (3 s), after which point the stimuli were removed. They could report their decision at any time during or after the stimulus presentation.…”
Section: Methodsmentioning
confidence: 99%
“…These results may seem to contradict a recent study by Tabrik and colleagues (2021). In that study, a great deal of similarity was found between the chosen shape metrics and the self-reported measures of perceptual similarity in both within-modal visual and within-modal haptic comparisons (different groups of participants were used for these tasks, so no cross-modal comparisons were possible).…”
Section: Discussioncontrasting
confidence: 74%
“…Previous work (Deshpande et al, 2010; Lacey et al, 2010) has indicated that the networks involved in haptic object recognition are similar to visual object recognition only when the shapes are familiar. This may also explain the results found in Tabrik et al (2021) where shapes were likely more familiar and greater similarity was found between visual and haptic processing as compared to the present study. Further work will seek to determine the extent to which stimulus familiarity impacts which metrics best predict human behavior.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation